The school in the cloud : the emerging future of learning - Mitra, Sugata, 1952- (Corwin, a SAGE Company, 2020)
"In 1999, Sugata Mitra conducted the famous "Hole in the Wall" experiment that inspired three TED Talks and earned him the first million-dollar TED prize for research. With this prize, Mitra has for the past three years been conducting new research around Self-Organized Learning Environments, building "Schools in the Cloud" all over the world. This new book still share the results of this research, how Schools in the Cloud work, what makes them successful, and how schools can build their own Schools in the Cloud"--